Homegarden improved avocado cultivation, income diversification, and food security for rural households in Central Ethiopia - Hadia Seid; John Kessy; A. Sigrun Dahlin; Zebene Asfaw (Cogent Economics & Finance)
Homegarden avocado cultivation offers a viable option for smallholder farmers to diversify their sources of income and food. This study examined the contribution of avocado cultivars to household income diversification and food security in the Jewe and Upper Gana kebeles of Central Ethiopia. Data were collected from 164 households using a semi-structured questionnaire and supplemented with focus group discussions. The results of this study indicated that Nabal, Hass, and Ettinger were the most commonly cultivated avocado cultivars. On average, the households owned four improved avocado trees. This study revealed that households had highly diversified income sources, with an average SID value of 0.63. The average fruit yields for the Nabal, Hass, and Ettinger cultivars ranged from 45 to 60 kg per household. These cultivars contributed approximately 14% and 10% of the household income sources and food consumption scores, respectively. This study found that, on average, households consumed 40 kg of Hass and 25 kg of Ettinger fruits, and sold 55 kg of Nabal and 25 kg of Ettinger fruits per harvest season. Improved avocado cultivation was positively associated with household income and food consumption. Local governments should encourage cultivation of these cultivars to enhance income and food security for farmers.